Soyasaponin Bb inhibits the recruitment of toll‐like receptor 4 (TLR4) into lipid rafts and its signaling pathway by suppressing the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase‐dependent generation of reactive oxygen species. Issue 7 (21st April 2016) - Zhang, Yajie; Chen, Fengping; Chen, Jiading; Huang, Suqun; Chen, Junbin; Huang, Jian; Li, Nan; Sun, Suxia; Chu, Xinwei; Zha, Longying
Abstract : Soyasaponins (SS) are triterpenoid‐based phytochemicals commonly found in soybean and its products. SSBb has previously been shown to inhibit inflammation through a mechanism related to the suppression of PI3K/Akt/NF‐κB and MAPKs signaling pathway. Here, we found that SSBb can inhibit TLR4 recruitment into lipid rafts and its signaling by suppressing the NADPH oxidase‐dependent reactive oxygen species generation, providing new understanding about the anti‐inflammatory effect of SS Abstract : Scope: We and others recently showed that soyasaponin Bb (SSBb ) inhibited lipopolysaccharide (LPS)‐induced inflammation in macrophages. Since the recruitment of toll‐like receptor 4 (TLR4) into lipid rafts is vital for LPS‐initiated signaling, we investigated whether this process would be modulated by SSBb . Methods and results: By using sucrose gradient ultracentrifuge, we found that pretreatment of macrophages with SSBb inhibited LPS‐induced recruitments of TLR4, myeloid differentiation primary response protein 88 (MyD88) and Toll/IL‐1 receptor domain‐containing adaptor inducing interferon‐β (TRIF) into fractions enriched with lipid rafts marker flotillin‐1. We also found SSBb decreased co‐localization of TLR4 and lipid rafts by utilizing confocal immunofluorescence microscopy. Additionally, we observed that SSBb suppressed LPS‐induced formation of TLR4/MyD88 and TLR4/TRIF complexes, production of pro‐inflammatory molecules, and activation of nuclear factor kappa B (NF‐κB). Furthermore, we found that these inhibitory effects of SSBb were associated with reduced reactive oxygen species (ROS) because pretreating cells with N‐acetyl‐L‐cysteine and NADPH oxidase inhibitor diphenyleneiodonium (DPI) inhibited LPS‐induced TLR4 recruitment into lipid rafts and NF‐κB activation. SSBb also inhibited NADPH oxidase activation by blocking interaction between gp91 phox and p47 phox similarly as DPI. Conclusion: SSBb can inhibit TLR4 recruitment into lipid rafts and its signaling by suppressing the NADPH oxidase‐dependent ROS generation.